Effect of Cold Diet and Diet at Room Temperature on Post-Tonsillectomy Pain in Children - Meybodian, Mojtaba (Iran J Otorhinolaryngol, 2019)
INTRODUCTION: The present study aimed to compare the effect of cold diet and diet at room temperature on post-tonsillectomy pain in children. MATERIALS AND METHODS: In the present study a total of 120 children within the age range of 4-12 years who underwent tonsillectomy were randomly assigned to two groups, namely group C with a cold-served diet and group room temperaturewith a room-temperature-served diet postoperatively. Each patient’s post-operative pain was evaluated using the Face, Legs, Activity, Cry, Consolability (FLACC) scale prior to oral diet initiation after the operation, before thesecond acetaminophen dose, before the next day breakfast, and before discharge. RESULTS: Out of 103 children, 48 and 55 children were femaleand male, respectively. The average age of the children was 7 years and 2 months. There was no significant difference in gender and age between the two groups. There were no significant differences in the mean scores of FLACC scale between the two groups at different times, including before starting an oral diet (P>0.15), before the second dose of acetaminophen (P>0.22), before the next day breakfast (P>0.32), and before discharge (P>0.83). In terms of bleedingfrequency, as well as nausea and vomiting, no significant difference was observed between the two groups. CONCLUSION: The obtained results of this study indicated that using cold liquids and foods after tonsillectomy did not have a significant effect on post-tonsillectomy pain in children. According to the findings, it is not rational to advise the mother or the child about the temperature of fluids and foods consumed post-tonsillectomy.